Flavonoid increase in soybean as a response to Nezara viridula injury and its effect on insect-feeding preference - Piubelli, G. C.; Hoffmann-Campo, C. B.; De Arruda, I. C.; Franchini, J. C.; Lara, F. M. (Kluwer Academic/plenum Publ, 2003)
The ability of the stink bug (Nezara viridula) to induce and/or increase production of chemical defenses, i.e., flavonoids, in immature seeds of five genotypes of soybean (BR-16, IAC-100, PI 227687, PI 229358, and PI 274454) was investigated under greenhouse and laboratory conditions. Samples from pods of each genotype damaged by stink bug were analyzed for flavonoid content with high performance liquid chromatography. A dual-choice test was conducted to evaluate the feeding preference of N. viridula comparing BR-16 pods treated with extracts of PI 227687 seeds (with and without stink-bug injury), with water-treated pods. Seeds of PI 227687 damaged by N. viridula presented the highest concentration (352 mug/g) of daidzin (4'-hydroxyisoflavone-7-glucoside). The same trend was observed with genistin (4',5,7-trihydroxyisoflavone-7-glucoside): PI 227687 contained 142.4 mug/g, PI 274454, 31.6 mug/g, and PI 229358, 38.9 mug/g. Seeds damaged by stink bugs had higher isoflavone contents (daidzin and genistin), compared to controls. However, after being damaged, PI 274454 and PI 229358 produced less genistin than the other genotypes and no differences in concentration between damaged and nondamaged plants of this genotypes were observed. The numbers of observations of the insect feeding and the numbers of stylet sheaths left in water-treated BR-16 pods were greater than in those treated with PI 227687 extracts. The insects fed for longer periods on BR-16 pods treated with extract of PI 227687 without injury compared to those that were treated with extract of PI 227687 previously injured by stink bugs. Extracts of PI 227687 pods ( damaged or not) were deterrent to adults of N. viridula, and insect injury increased concentrations of daidzin and genistin in PI 227687 seeds. The deterrence seemed to be more pronounced after pods had suffered stink-bug injury.
Keywords: resistance; green stink bug; Heteroptera; isoflavones; daidzin; genistin; deterrence